Analisis Pemberian Pembiayaan Kredit Usaha Rakyat (KUR) Pada PT. Bank BRI Syariah - Riffka Fauzany; Rakhmat Haryono (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2021)
Kredit Usaha Rakyat (KUR) itself is a credit or financing service provided by the government through banking to the UMKMK where the business has feasibility, potential, good business prospects, and has the ability to repay loans but is constrained in terms of capital. Some people's businesses that are expected to use KUR itself are covering all forms of business, especially businesses engaged in productive business sectors such as agriculture, fisheries and maritime affairs, industry, forestry, and savings and loan financial services. The method used is a descriptive analysis method that aims to make a description, description, or painting systematically, factually and accurately about the facts in the field. In addition, the research was carried out through a system of direct interviews with interested parties in this case the related companies. Furthermore, the process carried out by using Library Research in this study, researchers searched for library materials both through literature studies and through research journals that have variables that have similarities in this study. The discussion in this final project covers Procedures for Provision of People's Business Credit Financing, the requirements for applying for KUR credit are in accordance with what has been determined by the Government and analysis of the assessment of prospective KUR financing debtors using 6 C + 1S (character, capacity (capability), capital, condition of economy, collateral, constrains) and Syariah.